Green marketing mix as a catalyst for blue economy development: a strategic analysis in Samarinda - Fabiola Bulimasena Luturmas; Herdi Syam; Maulita Maulita (Institute of Computer Science (IOCS), 2026)
The green marketing mix encompasses environmentally friendly and recyclable marketing activities, including production processes, products, packaging, pricing, distribution, logistics, and promotion. The increasing significance of environmental issues has prompted stakeholders to prioritize sustainability in all systems and products. This approach aligns with the blue economy, which is closely associated with sustainable economic development and aims to ensure that current economic activities do not negatively affect future generations. As a result, future generations can continue to benefit from Indonesia’s abundant natural resources on both land and sea. However, in addressing present needs, environmental sustainability is often overlooked. The Mahakam River, which flows through Samarinda, serves as the city's primary water source and is vital to the community. It also functions as a transportation route for natural resources, particularly coal. This study analyzes the application of the green marketing mix in developing the blue economy in Samarinda, with the objective of increasing public awareness regarding the environmental impacts of economic activities and promoting environmental preservation. A qualitative research method was employed